2004
DOI: 10.1086/425371
|View full text |Cite
|
Sign up to set email alerts
|

Life‐History Variation Predicts the Effects of Demographic Stochasticity on Avian Population Dynamics

Abstract: Comparative analyses of avian population fluctuations have shown large interspecific differences in population variability that have been difficult to relate to variation in general ecological characteristics. Here we show that interspecific variation in demographic stochasticity, caused by random variation among individuals in their fitness contributions, can be predicted from a knowledge of the species' position along a "slow-fast" gradient of life-history variation, ranging from high reproductive species wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
115
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(128 citation statements)
references
References 43 publications
10
115
3
Order By: Relevance
“…Some studies have suggested that species with faster population growth are more likely to succeed in establishing, because such populations can rapidly escape the dangers of small population size (Moulton and Pimm 1986;Cassey 2002). In contrast, other studies have suggested that these species are likely to fail in establishment because they face higher stochastic demographic variance than those with lower growth rate (Saether et al 2004;Blackburn et al 2009a). Comparative studies of the relationship between establishment success and life history also suggest that species with slower population growth rates are more likely to succeed in establishing (Blackburn et al 2009b).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies have suggested that species with faster population growth are more likely to succeed in establishing, because such populations can rapidly escape the dangers of small population size (Moulton and Pimm 1986;Cassey 2002). In contrast, other studies have suggested that these species are likely to fail in establishment because they face higher stochastic demographic variance than those with lower growth rate (Saether et al 2004;Blackburn et al 2009a). Comparative studies of the relationship between establishment success and life history also suggest that species with slower population growth rates are more likely to succeed in establishing (Blackburn et al 2009b).…”
Section: Discussionmentioning
confidence: 98%
“…Our finding of a positive relationship between body mass and establishment success supports the latter view: features associated with slow population growth rates are more likely to determine whether or not introduced species succeed in establishing in Taiwan, following introduction. Such species may be more likely to establish because they are less susceptible to the negative effects of demographic and environmental stochasticity on small founding populations (Saether et al 2004;Blackburn et al 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in population size are most responsive to habitat loss during the period in which populations are more severely limited [3]. Unfortunately, relatively few empirical studies provide quantitative evidence indicating whether population size of migratory species is more sensitive to the amount of breeding habitat or non-breeding habitat [7,34,35] and we are unaware of any study done at range-wide scales.…”
Section: Discussionmentioning
confidence: 99%
“…Widespread species may be able to tolerate a broad range of environmental conditions (Gaston 2003), and the fact that they are likely to be moved to areas with high human population densities, as well as from such areas, increases the likelihood that they will find new locations to their liking (Blackburn et al 2009). Large-bodied, long-lived species may be less susceptible to the negative effects of demographic and environmental stochasticity (Saether et al 2004), whereas rapidly reproducing species can quickly escape the demographic and environmental traps associated with small populations (Moulton and Pimm 1986). This suggests that, deliberately or inadvertently, people have chosen alien mammal species with characteristics that may predispose them to success in the later stages of invasion.…”
Section: Discussionmentioning
confidence: 99%